Effect of zinc doping on the optoelectronic properties of cadmium sulphide (CdS) thin films deposited by chemical bath deposition by utilising an alternative sulphur precursor - Munna F.T.; Chelvanathan P.; Sobayel K.; Nurhafiza K.; Sarkar D.K.; Nour M.; Sindi H.; Rawa M.; Sopian K.; Amin N.; Akhtaruzzaman M. (Elsevier GmbH, 2023)
Cadmium sulfide; Cadmium sulfide solar cells; Chemical analysis; Deposition; Energy gap; II-VI semiconductors; Semiconductor doping; Thin film solar cells; Thioureas; Zinc; Zinc compounds; Chemical-bath deposition; Comparative analysis; Growth techniques; Optoelectrical properties; Optoelectronic properties; Solar cell devices; Solar cell structures; Zinc concentration; Thin films